2016
DOI: 10.1098/rspb.2016.1496
|View full text |Cite
|
Sign up to set email alerts
|

Spatially cascading effect of perturbations in experimental meta-ecosystems

Abstract: Ecosystems are linked to neighbouring ecosystems not only by dispersal, but also by the movement of subsidy. Such subsidy couplings between ecosystems have important landscape-scale implications because perturbations in one ecosystem may affect community structure and functioning in neighbouring ecosystems via increased/decreased subsidies. Here, we combine a general theoretical approach based on harvesting theory and a two-patch protist metaecosystem experiment to test the effect of regional perturbations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…Furthermore, roots in soil influence biogeochemical conditions together with root-associated microbes (Schade, Fisher, Grimm, & Seddon, 2001). This is consistent with previous fieldbased studies (Kaelin & Altermatt, 2016;Kautza & Sullivan, 2015;Krell et al, 2015;Seymour, Deiner, et al, 2016) and theoretical and experimental studies that predict the importance of cross-ecosystem exchange processes (Loreau et al, 2003) and patterns across landscapes (Harvey et al, 2016). Furthermore, Relative importance score (Pimm et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, roots in soil influence biogeochemical conditions together with root-associated microbes (Schade, Fisher, Grimm, & Seddon, 2001). This is consistent with previous fieldbased studies (Kaelin & Altermatt, 2016;Kautza & Sullivan, 2015;Krell et al, 2015;Seymour, Deiner, et al, 2016) and theoretical and experimental studies that predict the importance of cross-ecosystem exchange processes (Loreau et al, 2003) and patterns across landscapes (Harvey et al, 2016). Furthermore, Relative importance score (Pimm et al, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, local biodiversity in running waters is affected by various factors across multiple spatial scales, ranging from local to regional scales (Frissell, Liss, Warren, & Hurley, 1986;O'Neill, DeAngelis, Waide, & Allen, 1986;Poff, 1997). These factors include catchment hydrological processes that reflect upstream terrestrial conditions (Richards, Haro, Johnson, & Host, 1997), connections with adjacent riparian ecosystems (Harvey, Gounand, Ganesanandamoorthy, & Altermatt, 2016;Loreau, Mouquet, & Holt 2003;Soininen, Bartels, Heino, Luoto, & Hillebrand, 2015;Vannote, Minshall, Cummins, Sedell, & Cushing, 1980) and linkages of local environments in dendritic river networks (Altermatt, 2013;Altermatt, Seymour, & Martinez, 2013;Tonkin et al, 2018;Vannote et al, 1980;Ward, 1989). Previous studies reported that major ecological surprises sometimes emerge, as these multiple factors often cause nonlinear interactive effects in freshwater ecosystems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the facilitation treatment, the presence of the predator level and thus lead to a decline in detritus quality (increased in recalcitrant chitin content, see Gounand et al, 2017), with negative consequences for connected ecosystems (Gounand et al, 2017). Also, the presence of Euglena (facilitation treatment) generates a local enrichment effect, albeit limited by this species slow growth rate (Harvey et al, 2016). Overall, based on our results, downstream community dynamics seem to be mainly driven by variations in upstream bacteria densities (changes to subsidy quantity due to local upstream species dynamics), which likely acted in parallel to changes in resource quality and quantity from other internal dynamics in upstream ecosystems linked to our various community structure treatments (i.e., decreased quality in the Predation treatment and increased quantity in the Facilitation treatment).…”
Section: Discussionmentioning
confidence: 99%
“…As our focus is on the effect of different upstream community structures on downstream community dynamics, we use only the treatment rather than species names in the text for the sake of clarity and consistency. The choice of each species combination is based on prior knowledge from previous experiments in similar settings (Carrara, Giometto, Seymour, Rinaldo, & Altermatt, 2015;Gounand et al, 2017;Harvey et al, 2016). These five upstream communities were either connected to a downstream community composed of bacteria alone Each microcosm consisted of a 250-ml Schott bottle that was filled to 100 ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation